Comparative whole genome analysis of three consecutive Salmonella diarizonae isolates - Gerlach, Roman G.; Walter, Steffi; McClelland, Michael; Schmidt, Christiane; Steglich, Matthias; Prager, Rita; Bender, Jennifer K.; Fuchs, Stephan; Schoerner, Christoph; Rabsch, Wolfgang; Lang, Werner; Jantsch, Jonathan (International Journal of Medical Microbiology, 2017)
Infections of very young children or immunocompromised people with Salmonella of higher subspecies are a well-known phenomenon often associated with contact to cold-blooded animals. We describe the molecular characterization of three S. enterica subsp. diarizonae strains, isolated consecutively over a period of several months from a hospital patient suffering from diarrhea and sepsis with fatal outcome. With the initial isolate the first complete genome sequence of a member of subsp. diarizonae is provided and based on this reference we revealed the genomic differences between the three isolates by use of next-generation sequencing and confirmed by phenotypical tests. Genome comparisons revealed mutations within gpt, hfq and purK in the first isolate as a sign of clonal variation rather than host-directed evolution. Furthermore, our work demonstrates that S. enterica subsp. diarizonae possess, besides a conserved set of known Salmonella Pathogenicity Islands, a variable portfolio of additional genomic islands of unknown function.
EVALuna2:7731